The Effect of Olive Oil Administration on the Pruritus Scale in Chronic Kidney Disease Patients: A Quasi-Experimental Approach - Cahyati, Yanti; Triguna, Yudi; Riyana, Asep; Qibtia, Annisa Mariatul (PT. Pubsains Nur Cendekia, 2025)
Background: The kidneys are essential organs that regulate fluid and acid-base balance, metabolism, and the removal of toxins and waste from the body. If damaged, kidney function can be disrupted, and if this condition persists, it can develop into Chronic Kidney Disease (CKD). One of the therapies for chronic kidney failure patients is hemodialysis. Aims: To determine the effect of administering olive oil to CKD patients who experience pruritus. Method: This method uses a quantitative research method with a quasi-experimental approach, especially using the one-group pretest-posttest design. Sampling in this study used non-random sampling techniques, with purposive sampling, with a sample size of 60 people. The instrument used to measure the pruritus scale is the Numerical Rating Scale (NRS). The statistical test used is the Paired Sample t-test. Results: There is a difference in the average effect of the pruritus scale before and after administration of olive oil, with a Value of 0,000. Olive oil affects the pruritus scale in patients with chronic kidney failure. Conclusion: This study serves as a basis for implementing olive oil administration in chronic kidney disease patients experiencing pruritus.